Disrupted fine‐scale population processes in fragmented landscapes despite large‐scale genetic connectivity for a widespread and common cooperative breeder: the superb fairy‐wren (Malurus cyaneus). (28th November 2012) - Harrisson, Katherine A.; Pavlova, Alexandra; Amos, J. Nevil; Takeuchi, Naoko; Lill, Alan; Radford, James Q.; Sunnucks, Paul; Piertney, Stuart
Summary Understanding how habitat fragmentation affects population processes (e.g. dispersal) at different spatial scales is of critical importance to conservation. We assessed the effects of habitat fragmentation on dispersal and regional and fine‐scale population structure in a currently widespread and common cooperatively breeding bird species found across south‐eastern Australia, the superb fairy‐wren Malurus cyaneus. Despite its relative abundance and classification as an urban tolerant species, the superb fairy‐wren has declined disproportionately from low tree‐cover agricultural landscapes across the Box‐Ironbark region of north‐central Victoria, Australia. Loss of genetic connectivity and disruption to its complex social system may be associated with the decline of this species from apparently suitable habitat in landscapes with low levels of tree cover. To assess whether reduced structural connectivity has had negative consequences for genetic connectivity in the superb fairy‐wren, we used a landscape‐scale approach to compare patterns of genetic diversity and gene flow at large (landscape/regional) and fine (site‐level) spatial scales. In addition, using genetic distances, for each sex, we tested landscape models of decreased dispersal through treeless areas (isolation‐by‐resistance) while controlling for the effect of isolation‐by‐distance. Landscape models indicated that larger‐scale gene flow across the Box‐Ironbark region was constrained by distance rather than by lack of structural connectivity. Nonetheless, a pattern of isolation‐by‐resistance for males (the less‐dispersive sex) and lower genetic diversity and higher genetic similarity within sites in low‐cover fragmented landscapes indicated disruption to fine‐scale gene flow mechanisms and/or mating systems. Although loss of structural connectivity did not appear to impede gene flow at larger spatial scales, fragmentation appeared to affect fine‐scale population processes (e.g. local gene flow mechanisms and/or mating systems) adversely and may contribute to the decline of superb fairy‐wrens in fragmented landscapes in the Box‐Ironbark region.